3(x-5)=10x+6

Simple and best practice solution for 3(x-5)=10x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)=10x+6 equation:


Simplifying
3(x + -5) = 10x + 6

Reorder the terms:
3(-5 + x) = 10x + 6
(-5 * 3 + x * 3) = 10x + 6
(-15 + 3x) = 10x + 6

Reorder the terms:
-15 + 3x = 6 + 10x

Solving
-15 + 3x = 6 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-15 + 3x + -10x = 6 + 10x + -10x

Combine like terms: 3x + -10x = -7x
-15 + -7x = 6 + 10x + -10x

Combine like terms: 10x + -10x = 0
-15 + -7x = 6 + 0
-15 + -7x = 6

Add '15' to each side of the equation.
-15 + 15 + -7x = 6 + 15

Combine like terms: -15 + 15 = 0
0 + -7x = 6 + 15
-7x = 6 + 15

Combine like terms: 6 + 15 = 21
-7x = 21

Divide each side by '-7'.
x = -3

Simplifying
x = -3

See similar equations:

| 8m-5=5m+3 | | 3(-5)+y=-9 | | y=10x^2+50x+63.2 | | 4X+6Y=-2.5 | | x+x+13=57 | | Y=in(4x-5) | | -4x+4y=-3 | | 7(-z-10)=-63 | | 3(2g-3)-9g=-4g-6 | | m+4m-11m=30 | | -15p-6(4-4p)=6(p-4)-27 | | e=6x+12 | | 2y^2-10y+8=(y-4)(y-4) | | k^2-11k=-28 | | 6c+11=-2c-13 | | x-2y=4500 | | 5x-123=2 | | y=10x*2+50x+63.2 | | 6c+11=-2-13 | | Y-9=1(x-(-6)) | | 2x+6x=88 | | 2x+5y=1x+3y | | (4x)+-2=10 | | 42x+6(-2x-1)=5(x+6) | | 32x^2+32x=0 | | 2x^2+24x=-72 | | 20=1/2(70-x) | | v^2-21=4v | | 28-4x=12-8x | | 6(2+X)=2x+5 | | 3a=12-7a | | x=-5+5.1logd |

Equations solver categories